Pengaruh Ekspor, Impor, Nilai Tukar (Kurs) Dan Tingkat Inflasi Terhadap Cadangan Devisa Indonesia Periode 2016-2021 - Sucika Safitri; Agustina Mutia; Lidya Anggraeni (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to find out how the influence of exports, imports, exchange rates and inflation rates on Indonesia's foreign exchange reserves for the period 2016-2021. The type of research used is descriptive quantitative. Data collection is carried out using secondary data in the form of data on exports, imports, exchange rates, inflation rates and Indonesia's foreign exchange reserves for the period 2016-2021. The analytical method used in this study uses the classical assumption test and the multiple linear analysis method with time series data and processed with the SPSS 22 application. The results of this study indicate that the export variable partially has a positive and significant effect on Indonesia's foreign exchange reserves. The import variable partially has no significant effect on Indonesia's foreign exchange reserves. The exchange rate variable partially has a positive and significant effect on Indonesia's foreign exchange reserves. The inflation rate variable has no significant effect on Indonesia's foreign exchange reserves. Meanwhile, simultaneously, the variables of exports, imports, exchange rates and inflation rates have a significant effect on Indonesia's foreign exchange reserves.